#1**+3 **

Vertex form is a (x-h)^2 +k = 0 where h,k is the vertex so let's start with that h,k = 6,-1

a (x-6)^2 + -1 = y (this info was given in the question)

and the point 7,-3 given as a solution to this equation ..now we can substitute this into the equation to find 'a'

a(7-6)^2 -1 = -3

a-1 = -3

a=-2

so the equation becomes

-2(x-6)^2 -1 = y

ElectricPavlov Feb 20, 2018

#1**+3 **

Best Answer

Vertex form is a (x-h)^2 +k = 0 where h,k is the vertex so let's start with that h,k = 6,-1

a (x-6)^2 + -1 = y (this info was given in the question)

and the point 7,-3 given as a solution to this equation ..now we can substitute this into the equation to find 'a'

a(7-6)^2 -1 = -3

a-1 = -3

a=-2

so the equation becomes

-2(x-6)^2 -1 = y

ElectricPavlov Feb 20, 2018